Comparative study of 5% permethrin, 10% neem leaf extract, and 10% brotowali stem extract for scabies treatment - Widasmara, Dhelya; Yuniaswan, Anggun Putri; Listy Pramita, Vina (Frontiers in Medicine, 2025)
BackgroundScabies, a contagious skin infestation caused by Sarcoptes scabiei var. hominis, remains a significant public health issue, particularly in developing countries. Permethrin is the standard treatment; however, emerging limitations such as potential mite resistance highlight the need for effective alternatives.ObjectiveThis study compared the efficacy, safety, and quality-of-life impact of 5% permethrin lotion with 10% neem (Azadirachta indica) leaf extract lotion and 10% brotowali (Tinospora crispa) stem extract lotion among students in Islamic boarding schools, a population highly susceptible to recurrent scabies.MethodsA true experimental pre- and post-test controlled design was conducted involving 61 male students diagnosed with scabies. Participants were randomized into three treatment groups: 5% permethrin, 10% neem leaf extract, or 10% brotowali stem extract. The study was carried out from April to May 2021. Clinical improvement was assessed using lesion counts based on the Physician Global Assessment (PGA), while quality of life was evaluated using the Dermatology Life Quality Index (DLQI). Adverse effects were documented, and bivariate analyses were performed.ResultsAll three treatments significantly reduced lesion counts (p < 0.05), with no significant difference in median PGA scores between groups (p > 0.05). DLQI scores improved significantly in all groups, with earlier improvements observed by day 7 in the neem and brotowali groups. No adverse effects were reported.LimitationsTreatment adherence and exact application duration could not be fully controlled, and the possibility of reinfestation could not be excluded.ConclusionNeem leaf extract and brotowali stem extract lotions are as effective and safe as permethrin in treating scabies and improving patient quality of life. Both offer promising, affordable alternatives for scabies management in resource-limited settings.